La prime d’assurance - Moreau, Rémi (Assurances)

(untitled) (HEC Montréal, 1985)
The author reviews the main elements of the insurance premium from a legal and technical standpoint, in view of the applicable provisions of the civil code. In addition he explores the peculiarities of the premium, with respect to automobile insurance as well as the fiscal aspects. These thoughts on the premium, while in context with the new taxation on the premium, established on April 24th 1985, indicate that it is closely connected to the insurance transaction in its principles and applications.